2010
DOI: 10.1111/j.1600-0706.2010.18592.x
|View full text |Cite
|
Sign up to set email alerts
|

Breeding phenology determines evolutionary transitions in migratory behaviour in finches and allies

Abstract: The breeding season of longdistance migratory birds often starts later and is shorter than in resident or shortdistance species breeding at the same latitude, but the reason for this is unclear. Here we investigate the association between migration distance and breeding phenology in a group of passerine birds, the finches and their allies, using phylogenetic comparative methods. We confirm that migration distance is related to aspects of the species' breeding phenology after controlling for the effect of poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…By 1983, Guiguet (1983 listed sooty fox sparrows as resident on Vancouver Island, and other sources recognize them as residents of the Southern Gulf and San Juan Islands (Baron and Acorn 1997;Campbell et al 2001;Wahl et al 2005 well-known trade-offs in migratory and reproductive tactics, which influence species demography, ecology and evolution (Rolshausen et al 2009;Tökölyi and Barta 2011). Shifts from migratory to residential lifestyles have been linked to increases in reproductive effort (Gillis et al 2008;Bruderer and Salewski 2009).…”
mentioning
confidence: 99%
“…By 1983, Guiguet (1983 listed sooty fox sparrows as resident on Vancouver Island, and other sources recognize them as residents of the Southern Gulf and San Juan Islands (Baron and Acorn 1997;Campbell et al 2001;Wahl et al 2005 well-known trade-offs in migratory and reproductive tactics, which influence species demography, ecology and evolution (Rolshausen et al 2009;Tökölyi and Barta 2011). Shifts from migratory to residential lifestyles have been linked to increases in reproductive effort (Gillis et al 2008;Bruderer and Salewski 2009).…”
mentioning
confidence: 99%
“…Despite various published phylogenetic comparative analyses of numerous taxa that necessarily classified complex behavior at the species level (e.g., Olson et al 2008, Tökölyi and Barta 2011, Lapiedra et al 2013), we are not aware of studies addressing the consequences of inadequate classification in this approach. We argue that phylogenetic comparative analyses of shorebird mating strategies would result in more reliable conclusions if they allowed for variation within species and populations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a comparative study of shorebirds revealed an interaction between migration distance, latitude, and the length of the breeding season: the distance shorebirds from high latitudes migrate tends to decrease more rapidly as the egg-laying season lengthens than does the distance shorebirds from lower latitudes migrate (García-Peña et al 2009). More recently, Tökölyi and Barta (2011) found support for the correlated evolution of migratory behavior and breeding phenology and showed that both the onset of breeding and the length of the breeding season in small and medium-sized passerines is significantly correlated with migration distance. With its asynchronous breeding and migratory habits, the Red-necked Nightjar seems to be an appropriate model that may provide insight into the plasticity of breeding of species within narrow areas and to explore possible carry-over effects on the annual routines of migratory birds (see McNamara and Houston 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In relatively stable tropical regions, however, birds' breeding seasons are not only longer but also far more variable in duration than in temperate areas (Stutchbury and Morton 2001). Even though latitude has long been recognized to be an accurate predictor of birds' breeding phenology (Baker 1939), recent studies challenge conventional assumptions (see Stutchbury and Morton 2001) by showing how seasonal reproduction can be widely asynchronous both within a population and among populations inhabiting nearby areas, as a result of different habitat features (Aragonés et al 2001), genetic and cultural differentiation , or migratory behavior (Tökölyi and Barta 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation